Isolating membrane and preparation method thereof, secondary battery and electric device
Patent Information
- Application Number
- CN202380045621.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-31
- Filing Date
- 2023-04-12
- Publication Date
- 2025-01-28
AI Technical Summary
The isolation film of existing secondary batteries has poor heat resistance, which makes the battery prone to internal short circuit under high temperature conditions, increasing safety risks. At the same time, the mechanical strength and self-supporting performance are insufficient, affecting the reliability and production yield of the battery.
An isolation film structure including a first base film and a second base film is adopted, in which the melting point of the first base film is above 175°C and the average pore diameter is in the range of 0.22 μm-4.0 μm. Filler particles are embedded to form a composite structure and improve mechanical performance. Strength and heat resistance, and improve structural stability and breathability by adjusting the pore size and material selection of the second base membrane.
Significantly improve the safety performance, energy density and cycle performance of secondary batteries, reduce the probability of filler particles falling off, enhance the overall thickness and mechanical strength of the battery, and extend the cycle life of the battery.
Smart Images

Figure CN119384764A_ABST
Abstract
Description
Separator and preparation method thereof, secondary battery and electric device
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to international application PCT / CN2023 / 085617, filed on March 31, 2023, entitled “Isolation membrane and preparation method thereof, secondary battery and electrical device,” the entire contents of which are incorporated herein by reference. Technical Field
[0003] The present application relates to an isolation membrane and a preparation method thereof, a secondary battery and an electrical device. Background Art
[0004] In recent years, secondary batteries have been widely used in energy storage systems such as hydropower, thermal, wind, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. With the application and promotion of secondary batteries, the requirements for their reliability have become increasingly stringent.
[0005] Summary of the Invention
[0006] The present application provides an isolation membrane and a preparation method thereof, a secondary battery and an electrical device, aiming to improve the safety performance, energy density and cycle performance of the secondary battery.
[0007] In a first aspect, the present application provides an isolation film comprising a first base film, a second base film, and an intermediate layer, wherein the intermediate layer is positioned between the first and second base films. The first base film has a melting point of 175°C or higher and an average pore size of 0.22 μm or greater. The intermediate layer comprises filler particles, at least some of which are embedded in the first base film.
[0008] Without intending to be bound by any theory or explanation, when the separator includes a first base film, a second base film, and an intermediate layer located between the first base film and the second base film, the separator can have good heat resistance, high mechanical strength, and self-supporting properties. Specifically, the melting point of the first base film is above 175°C, which can provide the separator with good heat resistance. Furthermore, the average pore size of the first base film is within the above-mentioned suitable range, which can allow an appropriate amount of filler particles to be embedded in the first base film, forming a composite structure of the first base film and the filler particles, thereby effectively improving the mechanical strength, self-supporting properties, and heat resistance of the separator. In addition, after the filler particles are embedded in the base film, the overall thickness of the separator can be reduced, thereby further improving the energy density of the battery. Moreover, the specific pore size range allows the filler particles to be better embedded in the first base film, reducing the probability of the filler particles in the intermediate layer from falling off, thereby further improving the reliability of the separator and improving the cycle performance of the battery.
[0009] Therefore, the isolation membrane provided in the present application can enable the secondary battery to have better safety performance, higher energy density and good cycle performance at the same time.
[0010] In any embodiment of the present application, the average pore size of the first base film is 0.22 μm-4.0 μm, and can be optionally 1.0 μm-2.7 μm.
[0011] By adjusting the average pore size of the first base film to fall within the aforementioned range, filler particles can be easily embedded in the first base film, forming a suitable composite structure separator. This allows the separator to be thin while also exhibiting excellent air permeability and high strength. Consequently, the separator can be applied to secondary batteries, thereby improving their energy density and cycle performance.
[0012] In any embodiment of the present application, the average pore size of the second base film is smaller than the average pore size of the first base film.
[0013] Optionally, the average pore size of the second base film is 0.01 μm-0.5 μm, more optionally 0.02 μm-0.1 μm.
[0014] By adjusting the average pore size of the second base film to meet the above range, the second base film can have high mechanical strength, high puncture strength and appropriate permeability, thereby further improving the reliability of the secondary battery.
[0015] In any embodiment of the present application, the embedding depth of the filler particles in the first base film is greater than or equal to 0.2 μm, and can be optionally 0.5 μm-1.0 μm.
[0016] When the filler particles are embedded within the first base film to a depth within the aforementioned range, the mechanical strength and self-supporting properties of the composite structure formed by the filler particles and the first base film can be effectively enhanced, while also reducing the overall thickness of the separator in one step. This, in turn, helps improve the reliability and energy density of the secondary battery.
[0017] In any embodiment of the present application, the embedding depth of the filler particles in the second base film is greater than or equal to 0.1 μm, and can be optionally 0.1 μm-0.5 μm.
[0018] When the embedding depth of the filler particles in the second base film meets the above range, the structural stability of the separator can be improved, and the separator can have good air permeability and strength, thereby further improving the safety and electrochemical performance of the secondary battery.
[0019] In any embodiment of the present application, the embedding depth of the filler particles in the first base film is greater than the embedding depth of the filler particles in the second base film. This can provide the separator with high structural stability and good air permeability, thereby improving the reliability and electrochemical performance of the secondary battery.
[0020] In any embodiment of the present application, the melting point of the first base film is greater than or equal to the melting point of the second base film.
[0021] Optionally, the melting point of the first base film is 175°C-350°C, more preferably 220°C-350°C.
[0022] Optionally, the melting point of the second base film is 130°C-200°C, more preferably 135°C-180°C.
[0023] By adjusting the melting point of the first base film and / or the second base film within the above-mentioned suitable range, the separator can not only have good heat resistance but also good closed-cell properties. Thus, the secondary battery can achieve both good cycle performance and high reliability.
[0024] In any embodiment of the present application, the longitudinal elongation at break of the first base film is 20%-105%, and can be optionally 40%-90%.
[0025] In any embodiment of the present application, the transverse elongation at break of the first base film is 20%-105%, and can be optionally 40%-90%.
[0026] By adjusting the longitudinal elongation at break and / or transverse elongation at break of the first base film to meet the aforementioned ranges, the first base film can have a suitable average pore size, thereby facilitating the embedding of filler particles into the first base film and forming a suitable composite structure. This, in turn, improves the heat resistance and mechanical strength of the separator, thereby enhancing the reliability of the secondary battery.
[0027] In any embodiment of the present application, the longitudinal elongation at break of the second base film is less than the transverse elongation at break of the second base film.
[0028] In any embodiment of the present application, the longitudinal elongation at break of the second base film is ≥40%, and can be optionally 60%-150%.
[0029] In any embodiment of the present application, the transverse elongation at break of the second base film is ≥60%, and can be optionally 80%-160%.
[0030] Adjusting the longitudinal elongation at break and / or transverse elongation at break of the second base film to meet the aforementioned ranges can improve the ductility of the separator through the second base film, thereby improving the processability of the separator. This allows the separator to achieve both good processability and high heat resistance, thereby improving the production yield and reliability of secondary batteries.
[0031] In any embodiment of the present application, the porosity of the first base film is greater than the porosity of the second base film.
[0032] Optionally, the porosity of the first base film is 50%-98%.
[0033] Optionally, the porosity of the second base film is 20%-60%.
[0034] The porosity of the first base film and / or the second base film meets the given conditions, which can make the isolation membrane have good permeability and electrolyte infiltration performance, thereby improving the electrochemical performance and rate performance of the secondary battery.
[0035] In any embodiment of the present application, the relative molecular mass of the first base film is greater than the relative molecular mass of the second base film.
[0036] Optionally, the relative molecular mass of the first base film is 300,000-6,000,000, more preferably 1,000,000-3,000,000.
[0037] Optionally, the relative molecular mass of the second base film is 100,000-3,000,000, more preferably 400,000-1,500,000.
[0038] By adjusting the relative molecular mass of the first base film and / or the second base film to meet the above range, the melting point of the first base film and / or the second base film can be adjusted to meet the range of the embodiment of the present application, which is beneficial to improving the heat resistance of the isolation film and further improving the reliability of the secondary battery.
[0039] In any embodiment of the present application, the ratio of the thickness of the first base film to the thickness of the second base film is 0.15-2.0, and can be optionally 0.3-0.6.
[0040] Optionally, the thickness of the first base film is 1 μm-10 μm, more preferably 1 μm-3 μm.
[0041] Optionally, the second base film has a thickness of 2 μm-10 μm, more preferably 3 μm-6 μm.
[0042] When the thickness of the first base film and / or the second base film meets the above conditions, the isolation film can have a relatively small thickness while having a relatively high mechanical strength, thereby facilitating the secondary battery to have both high reliability and high energy density.
[0043] In any embodiment of the present application, the air permeability of the first base film is lower than the air permeability of the second base film.
[0044] Optionally, the ratio of the air permeability of the first base film to the air permeability of the second base film is 0.1-0.5, and more optionally 0.2-0.4.
[0045] Optionally, the air permeability of the first base film is 20sec / 100cc-100sec / 100cc, and more optionally 30sec / 100cc-40sec / 100cc.
[0046] Optionally, the air permeability of the second base film is 100sec / 100cc-300sec / 100cc, and more optionally 100sec / 100cc-150sec / 100cc.
[0047] By adjusting the permeability of the first base membrane and / or the second base membrane to meet the above range, the permeability of the first base membrane and the second base membrane can complement each other, so that the isolation membrane has appropriate permeability, thereby making the isolation membrane have good ion conductivity, thereby improving the electrochemical performance and rate performance of the secondary battery.
[0048] In any embodiment of the present application, the puncture strength of the first basement film is less than the puncture strength of the second basement film.
[0049] Optionally, the puncture strength of the first base film is 20 gf-150 gf, more preferably 20 gf-80 gf.
[0050] Optionally, the puncture strength of the second base film is 60 gf-400 gf, more preferably 80 gf-270 gf.
[0051] By adjusting the puncture strength of the first base film and / or the second base film to meet the above conditions, it is helpful to reduce the risk of the isolation film being punctured by lithium dendrites or being punctured under mechanical impact, thereby further improving the reliability of the secondary battery.
[0052] In any embodiment of the present application, the material of the first base film includes at least one of polytetrafluoroethylene and its derivatives, polyethylene terephthalate and its derivatives, polyimide and its derivatives, polyetheretherketone and its derivatives, polyphenylene sulfide and its derivatives, polybenzimidazole and its derivatives, polysulfone and its derivatives, and polylactic acid and its derivatives.
[0053] The material of the first base film is selected from the above-mentioned suitable substances, which is beneficial for the first base film to have a high melting point, thereby facilitating the improvement of the heat resistance of the isolation film, and further facilitating the improvement of the reliability of the secondary battery.
[0054] In any embodiment of the present application, the material of the second base film includes at least one of polyolefins, halogenated polyolefins, polyethers, polyesters, polyvinyl alcohol, polytetrafluoroethylene and its derivatives, polyethylene terephthalate and its derivatives, polyimides and their derivatives, polyetheretherketones and their derivatives, polyphenylene sulfide and its derivatives, polybenzimidazoles and their derivatives, and polysulfones and their derivatives.
[0055] The second base film is made of the aforementioned suitable materials, which helps the second base film better complement the first base film, allowing the separator to have both good heat resistance and high structural stability. This can further improve the reliability of the secondary battery and reduce the probability of safety accidents such as fire and explosion.
[0056] In any embodiment of the present application, the volume distribution particle size Dv50 of the filler particles is 0.01 μm-0.8 μm, and optionally 0.2 μm-0.8 μm. This is beneficial to improving the mechanical strength, self-supporting performance and heat resistance of the separator, thereby improving the reliability of the secondary battery.
[0057] In any embodiment of the present application, the content of the filler particles is less than or equal to 90%, and can be optionally 20%-80%, based on the total mass of the intermediate layer.
[0058] In any embodiment of the present application, the specific surface area of the filler particles is 2 g / m 2 -20g / m 2 , optional 6g / m 2 -9g / m 2 This is beneficial to improving the electrolyte infiltration performance of the separator, thereby reducing the internal resistance of the secondary battery, improving the cycle performance of the secondary battery, and extending the cycle life of the secondary battery.
[0059] In any embodiment of the present application, the filler particles include at least one of inorganic particles, organic particles, and organic-metal framework materials.
[0060] Optionally, the inorganic particles include one or more of inorganic particles having a dielectric constant of 5 or greater, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.
[0061] Optionally, the organic particles include one or more of polycarbonate, polythiophene, polypyridine, polystyrene, polyacrylic wax, polyethylene, polypropylene, cellulose, cellulose modifier, melamine resin, phenolic resin, polyester, silicone resin, polyimide, polyamideimide, polyaramid, polyphenylene sulfide, polysulfone, polyethersulfone, polyetheretherketone, polyaryletherketone, and copolymers of butyl acrylate and ethyl methacrylate.
[0062] Optionally, the organic-metal framework material includes one or more of a nitrogen-containing heterocyclic ligand building structure, an organic carboxylic acid ligand building structure, and a nitrogen-oxygen mixed ligand building structure.
[0063] In any embodiment of the present application, the intermediate layer also includes a binder, and the binder includes one or more of polyacrylate, polyacrylic acid, polyimide, polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-trichloroethylene copolymer, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, carboxymethyl cellulose, hydroxypropyl cellulose, regenerated cellulose, cellulose acetate, cellulose acetate propionate, cellulose acetate butyrate, polyacrylonitrile, polyvinyl alcohol, polyethylene, polypropylene, starch, cyanoethyl pullulan, thermoplastic polyurethane, maleic anhydride, and ethylene-acrylic acid copolymer.
[0064] Optionally, the content of the binder is less than or equal to 35%, more preferably 10%-30%, based on the total mass of the intermediate layer.
[0065] In any embodiment of the present application, the thickness of the separator is less than or equal to 7 μm, and can be optionally 3 μm-6 μm. The thickness of the separator is within the given range, which is conducive to further improving the energy density of the secondary battery.
[0066] Optionally, the air permeability of the separator is 100 sec / 100cc-300 sec / 100cc, or optionally 120 sec / 100cc-200 sec / 100cc. When the air permeability of the separator falls within the given range, the separator can have good ion conductivity, thereby enabling the secondary battery to have good electrochemical performance and rate performance.
[0067] Optionally, the transverse heat shrinkage rate of the isolation film at 250° C. for 1 hour is ≤1.0%, and optionally ≤0.4%.
[0068] Optionally, the longitudinal heat shrinkage rate of the isolation film at 250° C. for 1 hour is ≤1.0%, and optionally ≤0.3%.
[0069] Optionally, the transverse tensile strength of the isolation film is ≥0.5N, and can be optionally 1.2N-3.5N.
[0070] Optionally, the longitudinal tensile strength of the isolation film is ≥0.5N, and can be optionally 1.2N-3.5N.
[0071] When at least one of the transverse tensile strength, longitudinal tensile strength, transverse thermal shrinkage, and longitudinal thermal shrinkage of the separator meets the given range, the separator can have good heat resistance and physical properties, thereby improving the reliability of the secondary battery.
[0072] A second aspect of the present application provides a method for preparing the isolation membrane of the first aspect, comprising the following steps.
[0073] A first base film, a second base film and an intermediate layer slurry including filler particles are provided, wherein the melting point of the first base film is above 175° C. and the average pore size of the first base film is greater than or equal to 0.22 μm.
[0074] The intermediate layer slurry is coated on one of the first base film and the second base film and dried, and then laminated and hot-pressed with the other of the first base film and the second base film so that at least part of the filler particles are embedded in the first base film, thereby obtaining an isolation film.
[0075] Optionally, the slurry further comprises a binder.
[0076] In any embodiment of the present application, the drying temperature is 35°C-80°C, and can be optionally 40°C-60°C.
[0077] Optionally, the drying time is 5s-60s, optionally 5s-15s.
[0078] Optionally, the hot pressing temperature is 40°C-100°C, optionally 40°C-70°C.
[0079] Optionally, the hot pressing time is 5s-60s, optionally 5s-10s.
[0080] Optionally, the hot pressing pressure is 1 MPa-10 MPa, optionally 3 MPa-7 MPa.
[0081] A third aspect of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, and the separator of the first aspect, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet.
[0082] The secondary battery provided in the embodiment of the present application includes the isolation membrane of the first aspect of the present application. The isolation membrane can improve the reliability of the secondary battery and extend the cycle life of the secondary battery.
[0083] In any embodiment of the present application, the first base film of the separator faces the negative electrode. This facilitates the rapid passage of active ions (e.g., lithium ions), ensures the speed of lithium insertion, and promotes the uniformity of lithium insertion, which helps reduce the generation and growth of lithium dendrites, thereby further improving the safety performance of the battery.
[0084] A fourth aspect of the present application provides an electrical device comprising the secondary battery of the third aspect.
[0085] The electric device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] To more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.
[0087] FIG1 is a schematic diagram of an embodiment of a secondary battery provided by the present application.
[0088] FIG2 is an exploded schematic diagram of an embodiment of a secondary battery provided in the present application.
[0089] FIG3 is a schematic diagram of an embodiment of a battery module provided in the present application.
[0090] FIG4 is a schematic diagram of an embodiment of a battery pack provided in the present application.
[0091] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .
[0092] FIG6 is a schematic diagram of an embodiment of an electric device including the secondary battery provided in the present application as a power source.
[0093] In the accompanying drawings, which are not necessarily drawn to scale, the reference numerals are as follows: 1. battery pack; 2. upper housing; 3. lower housing; 4. battery module; 5. secondary battery; 51. housing; 52. electrode assembly; 53. cover plate. DETAILED DESCRIPTION
[0094] Below, the embodiments of the separator and its preparation method, secondary battery, and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially the same structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0095] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0096] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present application.
[0097] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of this application.
[0098] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0099] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0100] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0101] Unless otherwise specified, in this application, the terms "first", "second", etc. are used to distinguish different objects rather than to describe a specific order or a primary-secondary relationship.
[0102] In this application, the terms "plurality", "multiple" and the like refer to two or more.
[0103] Unless otherwise specified, the terms used in this application have the common meanings that are commonly understood by those skilled in the art.
[0104] Unless otherwise stated, the numerical values of the various parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise stated, the test temperature of each parameter is 25°C.
[0105] Unless otherwise specified, all ratio parameters involved in this application are compared in the same unit. For example, the thickness of A and B is 1.2:1, in which case the thickness of A and B has the same unit.
[0106] Isolation film
[0107] Typically, a secondary battery includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet, and mainly serves to prevent the positive and negative electrodes from short-circuiting.
[0108] The isolation film provided in the embodiments of the present application includes a first base film, a second base film, and an intermediate layer, wherein the intermediate layer is located between the first and second base films. The first base film has a melting point of 175°C or higher and an average pore size of 0.22 μm or greater. The intermediate layer includes filler particles, at least some of which are embedded in the first base film.
[0109] The separator membrane currently used in commercial secondary batteries is typically a polyolefin porous membrane, which has poor heat resistance. When heated, it undergoes a significant thermal shrinkage effect, which can cause direct contact between the positive and negative electrodes inside the battery, leading to internal short circuits and increasing the safety risks of the secondary battery. Compared to polyolefin porous membranes, the use of a first base membrane with a melting point above 175°C can effectively improve the heat resistance of the separator membrane. However, a first base membrane with a high melting point generally has lower mechanical strength and self-supporting properties, which may not meet the requirements of secondary battery processing, transportation, and use, resulting in reduced production yield and reliability of secondary batteries.
[0110] Without intending to be bound by any theory or explanation, when the separator includes a first base film, a second base film, and an intermediate layer located between the first base film and the second base film, the separator can have good heat resistance, high mechanical strength, and self-supporting properties. Specifically, the melting point of the first base film is above 175°C, which can provide the separator with good heat resistance. Furthermore, the average pore size of the first base film is within the above-mentioned suitable range, which can allow an appropriate amount of filler particles to be embedded in the first base film, forming a composite structure of the first base film and the filler particles, thereby effectively improving the mechanical strength, self-supporting properties, and heat resistance of the separator. In addition, after the filler particles are embedded in the base film, the overall thickness of the separator can be reduced, thereby further improving the energy density of the battery. Moreover, the specific pore size range allows the filler particles to be better embedded in the first base film, reducing the probability of the filler particles in the intermediate layer from falling off, thereby further improving the reliability of the separator and improving the cycle performance of the battery.
[0111] Therefore, the isolation membrane provided in the present application can enable the secondary battery to have better safety performance, higher energy density and good cycle performance at the same time.
[0112] In some embodiments, the average pore size of the first basement membrane can be 0.22 μm-4.0 μm, for example, it can be 0.22 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.5 μm, 2.7 μm, 3.0 μm, 3.5 μm, 4.0 μm, or a range consisting of any two of the above values. For example, the average pore size of the first base film may be 0.22 μm-3.5 μm, 0.22 μm-2.7 μm, 0.22 μm-2.5 μm, 0.22 μm-2.0 μm, 0.22 μm-1.8 μm, 0.22 μm-1.5 μm, 0.22 μm-1.0 μm, 0.22 μm-0.5 μm, 0.3 μm-4.0 μm, 0.3 μm-3.5 μm, 0.3 μm-2.7 μm, 0.3 μm-2.5 μm, 0.3 μm-2.0 μm, 0.3 μm-1.8 μm, 0.3 μm-1.5 μm, 0.3 μm-1.0 μm, 0.3 μm- 0.5μm, 0.5μm-4.0μm, 0.5μm-3.5μm, 0.5μm-2.7μm, 0.5μm-2.5μm, 0.5μm-2.0μm, 0.5μm-1.8μm, 0.5μm-1.5μm, 0.5μm-1.0μm, 0.8μm-4.0 μm, 0.8μm-3.5μm, 0.8μm-2.7μm, 0.8μm-2.5μm, 0.8μm-2.0μm, 0.8μm-1.8μm, 0.8μm-1.5μm, 1.0μm-4.0μm, 1.0μm-3.5μm, 1.0μm-2.7μm, 1.0μm-2.5μm, 1.0μm-2.0μm, 1.0μm-1.8μm, 1.0μm-1.5μm, 1.2μm-4.0μm, 1.2μm-3.5μm, 1.2μm-2.7μm, 1.2μm-2.5μm, 1.2μm-2.0μm, 1.2μm-1.8μm, 1.2μm-1.5μm, 1.5μm-4.0μm, 1.5μm-3.5μm, 1.5μm-2.7μm, 1.5μm-2.5μm, 1.5μm-2.0μm.
[0113] Without intending to be bound by any theory or explanation, adjusting the average pore size of the first base film to meet the above range facilitates the embedding of filler particles into the first base film, forming a suitable composite structure separator. This allows the separator to have a relatively thin thickness while also exhibiting excellent air permeability and high strength. Consequently, the separator can be applied to secondary batteries, thereby improving the energy density and cycle performance of the secondary batteries.
[0114] In some embodiments, the average pore size of the second base film is smaller than the average pore size of the first base film.
[0115] Optionally, in some embodiments, the average pore size of the second basement membrane may be 0.01 μm-0.5 μm, 0.01 μm-0.4 μm, 0.01 μm-0.3 μm, 0.01 μm-0.2 μm, 0.01 μm-0.1 μm, 0.02 μm-0.5 μm, 0.02 μm-0.4 μm, 0.02 μm-0.3 μm, 0.02 μm-0.2 μm, 0.02 μm-0.1 μm, 0.03 μm-0.1 μm, 0.04 μm-0.1 μm, 0.05 μm-0.1 μm.
[0116] Without intending to be bound by any theory or explanation, by adjusting the average pore size of the second base membrane to meet the above range, the second base membrane can be made to have high mechanical strength, high puncture strength and suitable permeability. Therefore, on the one hand, the mechanical strength of the separator can be improved by the second base membrane, thereby improving the structural stability of the separator and reducing the risk of the separator being pierced by lithium dendrites, resulting in a short circuit between the positive and negative electrodes; on the other hand, the permeability of the separator can be adjusted by the second base membrane, so that the separator has good barrier properties and reduces the risk of a short circuit caused by direct contact between the positive and negative electrodes. Therefore, the separator of the above embodiment is applied to secondary batteries, which can further improve the reliability of the secondary batteries.
[0117] The average pore size of the basement membrane has a well-known meaning in the art and can be measured using equipment and methods known in the art, for example, by referring to the test standard GB / T 21650-2008 and using a mercury porosimeter.
[0118] In some embodiments, the embedding depth of the filler particles in the first base film can be greater than or equal to 0.2 μm, for example, it can be 0.2 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1.0 μm, 1.1 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2.0 μm, or a range consisting of any two of the above values.
[0119] Optionally, in some embodiments, the embedding depth of the filler particles in the first base film may also be 0.5 μm-1.0 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, or a range consisting of any two of the above values.
[0120] Without intending to be bound by any theory or explanation, when the embedding depth of the filler particles in the first base film falls within the aforementioned range, the mechanical strength and self-supporting properties of the composite structure formed by the filler particles and the first base film can be effectively enhanced. This further improves the structural stability of the separator, thereby enhancing the reliability of the secondary battery. Furthermore, when the embedding depth of the filler particles in the first base film falls within the aforementioned range, the overall thickness of the separator can be further reduced, thereby further increasing the energy density of the battery.
[0121] In some embodiments, the embedding depth of the filler particles in the second base film may be greater than or equal to 0.1 μm, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, or a range consisting of any two of the above values.
[0122] Optionally, in some embodiments, the embedding depth of the filler particles in the second base film can be 0.1μm-0.5μm, for example, it can be 0.1μm, 0.15μm, 0.2μm, 0.25μm, 0.3μm, 0.35μm, 0.4μm, 0.45μm, 0.5μm, or a range consisting of any two of the above values.
[0123] Without intending to be bound by any theory or explanation, when the filler particles are embedded within the second base film to a depth within the aforementioned range, the intermediate layer and the second base film can maintain suitable bonding strength, thereby improving the structural stability of the separator. Furthermore, the second base film can maintain suitable air permeability and support properties, resulting in a separator with good air permeability and strength. This can further enhance the safety and electrochemical performance of the secondary battery.
[0124] In some embodiments, the embedding depth of the filler particles in the first base film may be greater than the embedding depth of the filler particles in the second base film.
[0125] Without intending to be limited by any theory or explanation, the embedding depth of the filler particles in the first base film is greater than the embedding depth of the filler particles in the second base film, which can make the isolation membrane have high structural stability and good air permeability, thereby improving the reliability and electrochemical performance of the secondary battery.
[0126] The embedding depth of the filler particles in the base film is a well-known meaning in the art and can be tested using equipment and methods known in the art. For example, it can be tested by using a scanning electron microscope (such as ZEISS Sigma 300). As an example, the following steps can be followed: first, the isolation film is cut into a sample to be tested of a certain size (for example, 6 mm × 6 mm), and the sample to be tested is clamped with two conductive and heat-conductive thin sheets (such as copper foil), and the sample to be tested and the thin sheets are glued and fixed with glue (such as double-sided tape), and a flat iron block of a certain mass (such as about 400 g) is used to press for a certain time (such as 1 hour) to make the gap between the sample to be tested and the copper foil as small as possible, and then the edges are trimmed with scissors and glued to a sample table with conductive glue, with the sample slightly protruding from the edge of the sample table. The sample stage is then placed into the sample holder and locked securely. An argon ion cross-section polisher (e.g., IB-19500CP) is powered on and vacuumed (e.g., 10 Pa to 4 Pa). The argon flow rate (e.g., 0.15 MPa), voltage (e.g., 8 kV), and polishing time (e.g., 2 hours) are set. The sample stage is then adjusted to rocking mode and polishing begins. After polishing, a scanning electron microscope (e.g., ZEISS Sigma 300) is used to obtain an ion-polished cross-sectional morphology (CP) image of the sample to be tested. The thickness of the base film and the intermediate layer are measured separately. The EDS mapping mode is then selected to measure the depth of the element (e.g., aluminum) contained in the filler particles within the base film as the embedment depth. For example, the midpoint of the element distribution curve can be used as the demarcation point, and the intermediate layer thickness can be substituted in. The intermediate layer thickness values on both sides of the midline are removed, resulting in the initial value. This value is then extended to the point where the element (e.g., aluminum) content in the filler particles reaches zero, and the resulting value is read as the embedment depth.
[0127] In some embodiments, the melting point of the first base film may be greater than or equal to the melting point of the second base film.
[0128] In some embodiments, the melting point of the first base film can be 175°C-350°C, for example, it can be 175°C, 200°C, 225°C, 250°C, 275°C, 300°C, 325°C, 350°C, or a range consisting of any two of the above values.
[0129] Optionally, in some embodiments, the melting point of the first base film can also be 220℃-350℃, for example, it can be 220℃, 230℃, 240℃, 250℃, 260℃, 270℃, 280℃, 290℃, 300℃, 310℃, 320℃, 330℃, 340℃, 350℃, or a range consisting of any two of the above values.
[0130] In some embodiments, the melting point of the second base film can be 130°C-200°C, for example, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, or a range consisting of any two of the above values.
[0131] Optionally, in some embodiments, the melting point of the second base film may be 135°C-180°C, for example, it may be 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C or a range consisting of any two of the above values.
[0132] Without intending to be bound by any theory or explanation, by adjusting the melting point of the first base film and / or the second base film within the above-mentioned suitable range, the separator can not only have good heat resistance, but also have good closed-pore properties. As a result, the separator not only has good ion conductivity when the secondary battery is operating normally, but also can close the pores in time to block current conduction when the secondary battery experiences thermal runaway. As a result, the secondary battery can achieve both good cycle performance and high reliability.
[0133] The melting point of the base film has a well-known meaning in the art and can be measured using equipment and methods known in the art. For example, it can be measured using differential scanning calorimetry. For details, please refer to the standard GB / T 19466.3-2004. As an example, the measurement can be performed as follows: 4 mg to 6 mg of the sample to be tested is placed in the sample chamber of a differential scanning calorimeter. The temperature is increased from 25°C to 400°C at a rate of 10°C / min. The melting endothermic curve of the sample is obtained, and the temperature corresponding to the peak of the curve is the melting point of the sample.
[0134] In some embodiments, the longitudinal elongation at break of the first base film can be 20%-105%, for example, it can be 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, 105%, or a range consisting of any two of the above values.
[0135] Optionally, in some embodiments, the longitudinal elongation at break of the first base film can also be 40%-90%, for example, it can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or a range consisting of any two of the above values.
[0136] In some embodiments, the transverse elongation at break of the first base film can be 20%-105%, for example, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, 105%, or a range consisting of any two of the above values.
[0137] Optionally, in some embodiments, the transverse elongation at break of the first base film can also be 40%-90%, for example, it can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or a range consisting of any two of the above values.
[0138] Without intending to be bound by any theory or explanation, when other intrinsic parameters of the first base film are substantially the same, a larger average pore size of the first base film is associated with a smaller longitudinal elongation at break and / or transverse elongation at break. Adjusting the longitudinal elongation at break and / or transverse elongation at break of the first base film to meet the aforementioned ranges facilitates the first base film having a suitable average pore size, thereby facilitating the embedding of filler particles into the first base film and forming a suitable composite structure. This improves the heat resistance and mechanical strength of the separator, thereby enhancing the reliability of the secondary battery.
[0139] The transverse elongation at break and the longitudinal elongation at break of the first base film have well-known meanings in the art and can be measured using equipment and methods known in the art. For example, both can be tested in accordance with standard GB / T 36363-2018.
[0140] In some embodiments, the longitudinal elongation at break of the second base film is less than the transverse elongation at break of the second base film.
[0141] The longitudinal elongation at break of the second base film can be greater than or equal to 40%, for example, it can be 40%, 50%, 60%, 70%, 80%, 90%, 100%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, or a range consisting of any two of the above values.
[0142] Optionally, in some embodiments, the longitudinal elongation at break of the second base film can be 60%-150%, for example, it can be 60%, 70%, 80%, 90%, 100%, 110%, 120%, 130%, 140%, 150%, or a range consisting of any two of the above values.
[0143] The transverse elongation at break of the second base film can be greater than or equal to 60%, for example, it can be 60%, 70%, 80%, 90%, 100%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, 190%, 200%, or a range consisting of any two of the above values.
[0144] Optionally, in some embodiments, the transverse elongation at break of the second base film can be 80%-160%, for example, it can be 80%, 90%, 100%, 110%, 120%, 130%, 140%, 150%, 160%, or a range consisting of any two of the above values.
[0145] Without intending to be bound by any theory or explanation, adjusting the longitudinal elongation at break and / or transverse elongation at break of the second base film to meet the aforementioned ranges can improve the ductility of the separator through the second base film, thereby improving the processability of the separator. This allows the separator to achieve both good processability and high heat resistance, thereby improving the production yield and reliability of secondary batteries.
[0146] The test method for the longitudinal elongation at break and / or the transverse elongation at break of the second base film may refer to the test method for the longitudinal elongation at break and / or the transverse elongation at break of the first base film.
[0147] In some embodiments, the porosity of the first base film may be greater than the porosity of the second base film.
[0148] Optionally, in some embodiments, the porosity of the first base film may be 30%-98%, for example, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, 98%, or a range consisting of any two of the above values.
[0149] Optionally, in some embodiments, the porosity of the second base film may be 20%-60%, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or a range consisting of any two of the above values.
[0150] Without intending to be bound by any theory or explanation, when the porosity of the first base film is greater than the porosity of the second base film, the porosities of the first base film and the second base film can complement each other, so that the porosity of the separator is within a suitable range, so that the separator has good permeability and electrolyte wetting performance, thereby improving the electrochemical performance and rate performance of the secondary battery. Furthermore, by adjusting the porosity of the first base film within the above-mentioned suitable range, the amount of filler particles embedded in the first base film can be appropriate, which not only helps to adjust the mechanical strength of the separator, but also enables the separator to have good air permeability. As a result, the separator of the embodiment of the present application not only has high reliability, but also has good ion conductivity. When applied to secondary batteries, it can improve the reliability, electrochemical performance and rate performance of the secondary battery. By adjusting the porosity of the second base film to meet the given range, it is beneficial to adjust the porosity of the separator within a suitable range, so that the separator has good permeability and electrolyte wetting performance, thereby improving the electrochemical performance and rate performance of the secondary battery.
[0151] The porosity of the base film has a well-known meaning in the art and can be measured using equipment and methods known in the art, for example, by using a mercury porosimeter according to the test standard GB / T 21650-2008.
[0152] In some embodiments, the relative molecular mass of the first base film may be greater than the relative molecular mass of the second base film.
[0153] Optionally, in some embodiments, the relative molecular mass of the first base film can be 300,000-6 million, for example, 300,000, 500,000, 800,000, 1 million, 2 million, 3 million, 4 million, 5 million, 6 million, or a range consisting of any two of the above values.
[0154] More optionally, in some embodiments, the relative molecular mass of the first basement membrane can also be 1 million-3 million, for example, it can be 1 million, 1.2 million, 1.5 million, 1.8 million, 2 million, 2.2 million, 2.5 million, 2.8 million, 3 million, or a range consisting of any two of the above values.
[0155] Optionally, in some embodiments, the relative molecular mass of the second base film can be 100,000-3 million, for example, it can be 100,000, 500,000, 800,000, 1 million, 1.5 million, 2 million, 1.5 million, 3 million, or a range consisting of any two of the above values.
[0156] More optionally, in some embodiments, the relative molecular mass of the second basement membrane can also be 400,000-1.5 million, for example, it can be 400,000, 600,000, 800,000, 1 million, 1.2 million, 1.4 million, 1.5 million, or a range consisting of any two of the above values.
[0157] It is not intended to be limited to any theory or explanation. By adjusting the relative molecular mass of the first base film and / or the second base film to meet the above-mentioned range, the melting point of the first base film and / or the second base film can be adjusted to meet the range of the embodiments of the present application, which is beneficial to improving the heat resistance of the isolation membrane and further improving the reliability of the secondary battery.
[0158] The relative molecular mass of the basement membrane has a well-known meaning in the art and can be measured using equipment and methods known in the art, for example, using a high-temperature GPC test (differential refractive index detector).
[0159] In some embodiments, the ratio of the thickness of the first base film to the thickness of the second base film can be 0.15-2.0, for example, 0.15, 0.3, 0.5, 1.0, 1.2, 1.5, 1.8, 2.0, or a range consisting of any two of the above values.
[0160] Optionally, in some embodiments, the ratio of the thickness of the first base film to the thickness of the second base film can also be 0.3-0.6, for example, it can be 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, or a range consisting of any two of the above values.
[0161] In some embodiments, the thickness of the first base film may be 1 μm-10 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or a range consisting of any two of the above values.
[0162] Optionally, in some embodiments, the thickness of the first base film may also be 1 μm-3 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, or a range consisting of any two of the above values.
[0163] In some embodiments, the thickness of the second base film may be 2 μm-10 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or a range consisting of any two of the above values.
[0164] Optionally, in some embodiments, the thickness of the second base film may also be 3 μm-6 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, or a range consisting of any two of the above values.
[0165] Without intending to be limited by any theory or explanation, when the thickness of the first base film and / or the second base film meets the above conditions, the isolation film can have a smaller thickness while having higher mechanical strength, thereby facilitating the secondary battery to have both high reliability and high energy density.
[0166] The thickness of the base film has a well-known meaning in the art and can be measured using equipment and methods known in the art. For example, six sets of parallel samples can be taken and the thickness of each set of samples can be measured at different locations using a micrometer thickness gauge. At least 20 locations are measured for each set of samples, and the average thickness of the six sets of samples is taken as the sample thickness.
[0167] In some embodiments, the air permeability of the first base film may be less than the air permeability of the second base film.
[0168] Optionally, in some embodiments, the ratio of the air permeability of the first base film to the air permeability of the second base film may be 0.1-0.5, 0.1-0.4, 0.1-0.3, 0.1-0.2, 0.2-0.5, 0.2-0.4, 0.2-0.3, 0.3-0.5, 0.3-0.4, 0.4-0.5.
[0169] In some embodiments, the air permeability of the first base film can be 20sec / 100cc-100sec / 100cc, for example, it can be 20sec / 100cc, 30sec / 100cc, 40sec / 100cc, 50sec / 100cc, 60sec / 100cc, 70sec / 100cc, 80sec / 100cc, 90sec / 100cc, 100sec / 100cc, or a range consisting of any two of the above values.
[0170] Optionally, in some embodiments, the air permeability of the first base film can also be 30sec / 100cc-40sec / 100cc, for example, it can be 30sec / 100cc, 32sec / 100cc, 34sec / 100cc, 36sec / 100cc, 38sec / 100cc, 40sec / 100cc, or a range consisting of any two of the above values.
[0171] In some embodiments, the air permeability of the second base film can be 100sec / 100cc-300sec / 100cc, for example, it can be 100sec / 100cc, 150sec / 100cc, 200sec / 100cc, 250sec / 100cc, 300sec / 100cc, or a range consisting of any two of the above values.
[0172] Optionally, in some embodiments, the air permeability of the second base film can also be 100sec / 100cc-150sec / 100cc, for example, it can be 100sec / 100cc, 110sec / 100cc, 120sec / 100cc, 130sec / 100cc, 140sec / 100cc, 150sec / 100cc, or a range consisting of any two of the above values.
[0173] Without intending to be bound by any theory or explanation, when the average pore size of the first base membrane falls within the range of the embodiments of this application, the first base membrane generally has a relatively low air permeability. By adjusting the air permeability of the first base membrane and / or the second base membrane to fall within the above range, the air permeabilities of the first base membrane and the second base membrane can complement each other, resulting in an appropriate air permeability of the separator, thereby providing the separator with good ion conductivity, thereby improving the electrochemical performance and rate performance of the secondary battery.
[0174] The air permeability of the base film has a well-known meaning in the art and can be measured using equipment and methods known in the art. For example, it can be tested with reference to GB / T 36363-2018.
[0175] In some embodiments, the puncture strength of the first basement membrane may be less than the puncture strength of the second basement membrane. For example, the ratio of the puncture strength of the first basement membrane to the puncture strength of the second basement membrane may be 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 0.98, 0.99, or a range consisting of any two of the above values.
[0176] In some embodiments, the puncture strength of the first base film can be 20 gf-150 gf, for example, 20 gf, 40 gf, 60 gf, 80 gf, 100 gf, 120 gf, 150 gf, or a range consisting of any two of the above values.
[0177] Optionally, in some embodiments, the puncture strength of the first basement membrane may also be 20gf-80gf, for example, 20gf, 30gf, 40gf, 50gf, 60gf, 70gf, 80gf, or a range consisting of any two of the above values.
[0178] In some embodiments, the puncture strength of the second base film can be 60 gf-400 gf, for example, 60 gf, 100 gf, 150 gf, 200 gf, 250 gf, 300 gf, 350 gf, 400 gf, or a range consisting of any two of the above values.
[0179] Optionally, in some embodiments, the puncture strength of the second basement membrane can also be 80gf-270gf, for example, it can be 80gf, 100gf, 120gf, 150gf, 180gf, 200gf, 220gf, 250gf, 270gf, or a range consisting of any two of the above values.
[0180] By adjusting the puncture strength of the first base film and / or the second base film to meet the above conditions, it is helpful to reduce the risk of the isolation film being punctured by lithium dendrites or being punctured under mechanical impact, thereby further improving the reliability of the secondary battery.
[0181] The puncture strength of the basement membrane has a meaning well known in the art and can be measured using equipment and methods known in the art. For example, the test can be performed with reference to GB / T 10004-2008. Specifically, the basement membrane can be cut into strips to obtain a test piece, and the width of the test piece can be 100 mm. A test piece with a width of 100 mm is mounted on a sample membrane fixing clamp ring, and then a steel needle with a diameter of 1.0 mm and a radius of 0.5 mm at the top of the diameter is used to puncture the test piece at a speed of (50±5) mm / min, and the maximum load of the steel needle penetrating the test piece is read. More than 5 groups of parallel samples can be taken, and 3 points of each group of samples are randomly tested. The arithmetic mean of the puncture strength of all parallel samples is taken as the puncture strength of the basement membrane.
[0182] In some embodiments, the material of the first base film includes at least one of polytetrafluoroethylene (PTFE) and its derivatives, polyethylene terephthalate (PET) and its derivatives, polyimide (PI) and its derivatives, polyetheretherketone (PEEK) and its derivatives, polyphenylene sulfide (PPS) and its derivatives, polybenzimidazole (PBI) and its derivatives, polysulfone (PSF) and its derivatives, and polylactic acid (PLA) and its derivatives.
[0183] Optionally, in some embodiments, the first base film includes polytetrafluoroethylene or a derivative of polytetrafluoroethylene.
[0184] Derivatives usually refer to products derived from polymers in which hydrogen atoms or atomic groups are replaced by other atoms or atomic groups.
[0185] Without intending to be bound by any theory or explanation, the material of the first base film is selected from the above-mentioned suitable substances, which is conducive to the first base film having a high melting point, thereby facilitating the improvement of the heat resistance of the isolation membrane, and further facilitating the improvement of the reliability of the secondary battery. In particular, when the first base film is a polytetrafluoroethylene-based film, in the event of thermal runaway of the secondary battery, even if the internal temperature of the battery is higher than the melting point of the polytetrafluoroethylene-based film, causing the polytetrafluoroethylene-based film to melt, the polytetrafluoroethylene-based film will not be melted or undergo significant shrinkage, thereby allowing the isolation membrane to have high structural stability. As a result, the isolation membrane can effectively block the contact between the positive and negative electrodes when the secondary battery undergoes thermal runaway, thereby further improving the reliability of the secondary battery and reducing the probability of safety accidents such as fire and explosion in the secondary battery.
[0186] In some embodiments, the material of the second base film may include at least one of polyolefins, halogenated polyolefins, polyethers, polyesters, polyvinyl alcohol, polytetrafluoroethylene and its derivatives, polyethylene terephthalate and its derivatives, polyimides and their derivatives, polyetheretherketones and their derivatives, polyphenylene sulfide and its derivatives, polybenzimidazoles and their derivatives, and polysulfones and their derivatives.
[0187] The second base film is made of the aforementioned suitable materials, which helps the second base film better complement the first base film, allowing the separator to have both good heat resistance and high structural stability. This can further improve the reliability of the secondary battery and reduce the probability of safety accidents such as fire and explosion.
[0188] In some embodiments, the volume distribution particle size Dv50 of the filler particles can be 0.01 μm-0.8 μm, for example, 0.01 μm, 0.05 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, or a range consisting of any two of the above values.
[0189] Optionally, in some embodiments, the volume distribution particle size Dv50 of the filler particles can also be 0.2μm-0.8μm, for example, it can be 0.2μm, 0.25μm, 0.3μm, 0.35μm, 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm, 0.65μm, 0.7μm, 0.75μm, 0.8μm, or a range consisting of any two of the above values.
[0190] Without intending to be bound by any theory or explanation, when the volume distribution particle size Dv50 of the filler particles falls within the above range, they can better match the pore structure of the first base film surface, thereby forming a suitable composite structure with the first base film. This helps improve the mechanical strength, self-supporting properties, and heat resistance of the separator, thereby improving the reliability of the secondary battery.
[0191] The volume distribution particle size Dv50 of the filler particles has a well-known meaning in the art and may represent the particle size corresponding to the 50% cumulative particle size distribution percentage in the volume-based particle size distribution of the filler particles. The volume distribution particle size Dv50 can be measured using equipment and methods known in the art. For example, it can be measured using a laser particle size analyzer (e.g., Malvern Mastersizer 2000E, UK), in accordance with GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method.
[0192] In some embodiments, the filler particles may have a specific surface area of 2 g / m 2 -20g / m 2 , for example, it can be 2g / m 2 , 5g / m 2 , 8g / m 2 , 10g / m 2 , 12g / m 2 , 15g / m 2 , 18g / m 2 , 20g / m 2 , or a range consisting of any two of the above values.
[0193] Optionally, in some embodiments, the specific surface area of the filler particles may also be 6 g / m 2 -9g / m 2 , for example, it can be 6g / m 2 , 7g / m 2 , 8g / m 2 , 9g / m 2 , 10g / m 2 , or a range consisting of any two of the above values.
[0194] It is not intended to be limited to any theory or explanation. By adjusting the specific surface area of the filler particles within the above-mentioned appropriate range, not only can a suitable composite structure be formed between the filler particles and the first base film, thereby improving the mechanical strength, self-supporting performance and heat resistance of the isolation membrane, but it is also beneficial to improve the electrolyte infiltration performance of the isolation membrane, thereby helping to reduce the internal resistance of the secondary battery, improve the cycle performance of the secondary battery, and extend the cycle life of the secondary battery.
[0195] The specific surface area of filler particles has a well-known meaning in the art and can be measured by methods known in the art, for example, by using a specific surface area analyzer (such as Tristar II 3020M) and nitrogen adsorption / desorption method.
[0196] In some embodiments, the filler may include at least one of inorganic particles, organic particles, and organic-metal framework materials.
[0197] Alternatively, the inorganic particles may include one or more of inorganic particles having a dielectric constant of 5 or greater, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.
[0198] Alternatively, the organic particles may include one or more of polycarbonate, polythiophene, polypyridine, polystyrene, polyacrylic wax, polyethylene, polypropylene, cellulose, a cellulose modifier (e.g., carboxymethyl cellulose), a melamine resin, a phenolic resin, a polyester (e.g., polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), a silicone resin, a polyimide, a polyamideimide, a polyaramid, polyphenylene sulfide, a polysulfone, a polyethersulfone, a polyetheretherketone, a polyaryletherketone, a copolymer of butyl acrylate and ethyl methacrylate (e.g., a cross-linked polymer of butyl acrylate and ethyl methacrylate).
[0199] Optionally, the organic-metal framework material may include one or more of a nitrogen-containing heterocyclic ligand building structure, an organic carboxylic acid ligand building structure, and a nitrogen-oxygen mixed ligand building structure.
[0200] In some embodiments, the intermediate layer may further include a binder, which can ensure the adhesion strength and uniformity between the first base film and the second base film while imparting good heat resistance to the separator, thereby improving the reliability of the secondary battery.
[0201] In some embodiments, the binder may include one or more of polyacrylate, polyacrylic acid, polyimide, polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-trichloroethylene copolymer, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, carboxymethyl cellulose, hydroxypropyl cellulose, regenerated cellulose, cellulose acetate, cellulose acetate propionate, cellulose acetate butyrate, polyacrylonitrile, polyvinyl alcohol, polyethylene, polypropylene, starch, cyanoethyl pullulan, thermoplastic polyurethane, maleic anhydride, and ethylene-acrylic acid copolymer.
[0202] In some embodiments, based on the total mass of the intermediate layer, the content of the filler particles may be less than or equal to 90%, and optionally 20%-80%.
[0203] In some embodiments, based on the total mass of the intermediate layer, the content of the binder may be less than or equal to 35%, and may be optionally 10%-30%.
[0204] In some embodiments, the intermediate layer may further include a dispersant, such as carboxymethyl cellulose, to adjust the viscosity of the intermediate layer slurry and improve the quality and uniformity of the film layer.
[0205] In some embodiments, the thickness of the isolation film may be less than or equal to 7 μm. Alternatively, in some embodiments, the thickness of the isolation film may be 3 μm-6 μm. A thickness of the isolation film within the given range is beneficial for further improving the energy density of the secondary battery.
[0206] The test method for the thickness of the isolation film can refer to the test method for the thickness of the base film.
[0207] In some embodiments, the air permeability of the separator can be 100 sec / 100cc-300 sec / 100cc, and optionally 120 sec / 100cc-200 sec / 100cc. When the air permeability of the separator falls within the given range, the separator can have good ion conductivity, thereby enabling the secondary battery to have good electrochemical performance and rate performance.
[0208] The test method for the air permeability of the isolation film can refer to the test method for the air permeability of the base film.
[0209] In some embodiments, the transverse heat shrinkage rate of the isolation film at 250° C. for 1 hour may be less than or equal to 1.0%, and optionally less than or equal to 0.4%.
[0210] In some embodiments, the longitudinal thermal shrinkage rate of the isolation film at 250° C. for 1 hour may be less than or equal to 1.0%, and optionally less than or equal to 0.3%.
[0211] In some embodiments, the transverse tensile strength of the isolation film may be greater than or equal to 0.5N, and may be optionally 1.2N-3.5N.
[0212] In some embodiments, the longitudinal tensile strength of the isolation film may be greater than or equal to 0.5N, and may be optionally 1.2N-3.5N.
[0213] When at least one of the transverse tensile strength, longitudinal tensile strength, transverse thermal shrinkage, and longitudinal thermal shrinkage of the separator meets the given range, the separator can have good heat resistance and physical properties, thereby improving the reliability of the secondary battery.
[0214] The transverse heat shrinkage, longitudinal heat shrinkage, transverse tensile strength, and longitudinal tensile strength of the separator have well-known meanings in the art and can be measured using methods known in the art. For example, they can be tested in accordance with GB / T 36363-2018.
[0215] Preparation method
[0216] The embodiments of the present application also provide a method for preparing the isolation film provided in the embodiments of the present application.
[0217] The method includes the following steps: providing a first base film, a second base film, and an intermediate layer slurry including filler particles, wherein the first base film has a melting point of 175°C or higher and an average pore size of 0.22 μm or greater; coating the intermediate layer slurry on one of the first and second base films and drying it; then laminating and heat-pressing the intermediate layer slurry with the other of the first and second base films so that at least a portion of the filler particles are embedded in the first base film, thereby forming a separator. Optionally, the slurry also includes a binder.
[0218] In some embodiments, the drying temperature can be 35°C-80°C, 35°C-70°C, 35°C-60°C, 35°C-50°C, 40°C-70°C, 40°C-60°C, 40°C-50°C, 50°C-80°C, 50°C-70°C, 50°C-60°C, 60°C-80°C.
[0219] In some embodiments, the drying time may be 5s-60s, 5s-45s, 5s-30s, 5s-15s, 15s-60s, 15s-45s, 15s-30s.
[0220] In some embodiments, the hot pressing temperature may be 40°C-100°C, 40°C-85°C, 40°C-70°C, 40°C-60°C, 50°C-100°C, 50°C-85°C, 50°C-70°C.
[0221] In some embodiments, the hot pressing time may be 5s-60s, 5s-40s, 5s-20s, 5s-10s, 10s-60s, 10s-40s, 10s-20s.
[0222] In some embodiments, the hot pressing pressure may be 1 MPa-10 MPa, 2 MPa-8 MPa, 3 MPa-7 MPa, or 4 MPa-6 MPa.
[0223] By adjusting the separator preparation parameters, such as drying parameters and hot pressing parameters, the separator formed by the composite of the first base film, the intermediate layer, and the second base film can exhibit excellent mechanical strength, self-supporting properties, and heat resistance. Furthermore, by adjusting the separator hot pressing parameters within the aforementioned ranges, the embedding depth of the filler particles within the base film can be adjusted, thereby reducing the overall thickness of the separator and further improving the battery's energy density.
[0224] In some embodiments, the coating method of the intermediate layer slurry can be transfer coating, spin spray coating, dip coating, etc., which is not limited in the embodiments of the present application.
[0225] Unless otherwise specified, all raw materials used in the method for preparing the separator (eg, the first base film, the second base film, filler particles, adhesive, etc.) can be purchased commercially.
[0226] secondary batteries
[0227] An embodiment of the present application also provides a secondary battery.
[0228] Secondary batteries, also known as rechargeable batteries or storage batteries, are batteries that can be recharged after discharge to reactivate the active materials and continue to be used. Typically, a secondary battery consists of an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is placed between the positive and negative electrodes to prevent short circuits between the positive and negative electrodes while allowing active ions to pass through.
[0229] The present application has no particular limitation on the type of secondary battery. For example, the secondary battery may be a lithium ion battery, a sodium ion battery, a lithium metal battery, a sodium metal battery, etc. In particular, the secondary battery may be a lithium ion battery.
[0230] The secondary battery provided in the embodiments of the present application includes the isolation membrane described above or the isolation membrane prepared by the method described above. The isolation membrane can improve the reliability of the secondary battery and extend the cycle life of the secondary battery.
[0231] [Positive electrode]
[0232] In some embodiments, the positive electrode sheet may include a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector and comprising a positive electrode active material. For example, the positive electrode current collector may have two opposing surfaces in its thickness direction, and the positive electrode film layer may be disposed on either or both of the two opposing surfaces of the positive electrode current collector.
[0233] When the secondary battery is a lithium-ion battery, the positive electrode active material may include, but is not limited to, at least one of a lithium transition metal oxide, a lithium-containing phosphate, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.
[0234] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium ion battery may include a general formula of Li a Ni b Co c M d O e A f At least one of lithium transition metal oxides and modified compounds thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M is selected from at least one of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A is selected from at least one of N, F, S and Cl.
[0235] As an example, the positive active material for lithium ion batteries may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523),LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 At least one of O2, LiFePO4, and LiMnPO4.
[0236] When the secondary battery is a sodium ion battery, the positive electrode active material may include but is not limited to at least one of sodium-containing transition metal oxides, polyanion materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue materials.
[0237] As an example, the positive active material for sodium ion batteries may include NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2 Ti 1 / 2 O2、NaNi 1 / 2 Mn 1 / 2 O2、Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2、NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue materials, general formula X p M' q (PO4) r O x Y 3-x At least one of the materials. p M' q (PO4) r O x Y 3-x , 0<p≤4, 0<q≤2, 1≤r≤3, 0≤x≤2, X is selected from H + 、Li + 、Na + , K + and NH4 + At least one of , M' is a transition metal cation, optionally at least one of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, and Y is a halogen anion, optionally at least one of F, Cl and Br.
[0238] The modified compounds of the above-mentioned positive electrode active materials may be used to perform doping modification and / or surface coating modification on the positive electrode active materials.
[0239] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application does not particularly limit the type of the positive electrode conductive agent. For example, the positive electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0240] In some embodiments, the positive electrode film layer may further optionally include a positive electrode binder. This application does not particularly limit the type of positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin.
[0241] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of aluminum, an aluminum alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0242] The positive electrode film is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying it, and cold pressing it. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).
[0243] [Negative electrode]
[0244] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and comprising a negative electrode active material. For example, the negative electrode current collector may have two opposing surfaces in its thickness direction, and the negative electrode film layer may be disposed on either or both of the two opposing surfaces of the negative electrode current collector.
[0245] The negative electrode active material may be any negative electrode active material known in the art for use in secondary batteries. For example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. Silicon-based materials may include at least one of elemental silicon, silicon oxide, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include at least one of elemental tin, tin oxide, and tin alloys.
[0246] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0247] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. The present application does not particularly limit the type of the negative electrode binder. As examples, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0248] In some embodiments, the negative electrode film layer may further include other additives, such as thickeners, sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like.
[0249] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, a copper alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0250] The negative electrode film layer is typically formed by coating the negative electrode slurry onto the negative electrode current collector, drying it, and cold pressing it. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring them uniformly. The solvent can be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.
[0251] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some embodiments, the negative electrode plate of the present application also includes a protective layer covering the surface of the negative electrode film layer.
[0252] [Electrolyte]
[0253] During the charge and discharge process of a secondary battery, active ions are embedded and released back and forth between the positive and negative electrodes, and the electrolyte conducts the active ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte, and the electrolyte can be selected according to actual needs.
[0254] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not particularly limited and can be selected according to actual needs.
[0255] When the secondary battery is a lithium ion battery, as an example, the electrolyte salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0256] When the secondary battery is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bisfluorosulfonyl imide (NaFSI), sodium bistrifluoromethanesulfonyl imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobisoxalatophosphate (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).
[0257] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), and diethyl sulfone (ESE).
[0258] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.
[0259] In some embodiments, the positive electrode sheet, the separator and the negative electrode sheet can be made into an electrode assembly by a winding process and / or a lamination process. It can be understood that the separator of the present application includes both a first base film and a second base film, and the first base film or the second base film can optionally face the positive electrode sheet or the negative electrode sheet. For example, the first base film faces the positive electrode sheet, and the second base film faces the negative electrode sheet; or the first base film faces the negative electrode sheet, and the second base film faces the positive electrode sheet. In order to further improve the safety performance of the battery, in the secondary battery of the present application, the first base film of the separator can face the negative electrode sheet, and the second base film faces the positive electrode sheet. The inventors have found that the pore size of the first base film in the separator of the present application is within a specific range. When it faces the negative electrode, it is more conducive to the rapid passage of active ions (such as lithium ions), ensuring the speed of lithium insertion and being conducive to the uniformity of lithium insertion, which is conducive to reducing the generation and growth of lithium dendrites, thereby further improving the safety performance of the battery.
[0260] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0261] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0262] The present application has no particular limitation on the shape of the secondary battery, which can be cylindrical, square, or any other shape. FIG1 shows a secondary battery 5 with a square structure as an example.
[0263] In some embodiments, as shown in FIG2 , the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can be formed into an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.
[0264] Methods for preparing secondary batteries are well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a secondary battery. For example, the positive electrode sheet, separator, and negative electrode sheet can be wound and / or laminated to form an electrode assembly. The electrode assembly is then placed in an outer package, dried, and then injected with electrolyte. The secondary battery is then vacuum packaged, allowed to stand, formed, and shaped.
[0265] In some embodiments, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0266] Figure 3 is a schematic diagram of an exemplary battery module 4. As shown in Figure 3 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured using fasteners.
[0267] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0268] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0269] Figures 4 and 5 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 4 and 5, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0270] Electrical devices
[0271] The embodiments of the present application also provide an electrical device, which includes at least one of the secondary batteries, battery modules, or battery packs provided in the embodiments of the present application. The secondary batteries, battery modules, or battery packs can be used as power sources for the electrical device, or as energy storage units for the electrical device. The electrical device can be, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0272] The electrical device can select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0273] Figure 6 is a schematic diagram of an exemplary electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module may be used.
[0274] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a secondary battery as a power source.
[0275] Example
[0276] The following examples describe the present disclosure in more detail. These examples are intended to be illustrative only, as various modifications and variations within the scope of the present disclosure will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing. The instruments used in the examples are commercially available.
[0277] Example 1
[0278] Preparation of isolation membrane
[0279] A first base film and a second base film are provided. The first base film is made of PTFE, has a melting point of 327°C, an average pore size of 0.22 μm, a porosity of 87%, and a thickness of 2.8 μm. The second base film is made of PE, has a melting point of 142°C, an average pore size of 0.03 μm, a porosity of 33%, and a thickness of 5 μm.
[0280] Providing an intermediate layer slurry: Filler boehmite particles, binder polyacrylate, and carboxymethyl cellulose are mixed uniformly in a mass ratio of 4:1:1 in an appropriate amount of deionized water to form an intermediate layer slurry. The volume distribution particle size Dv50 of the filler boehmite particles is 0.2 μm.
[0281] The intermediate layer slurry is coated on the PTFE base membrane and dried, and the PE base membrane and the PTFE base membrane are hot-pressed to form a separation membrane with the intermediate layer between the PTFE base membrane and the PE base membrane. The drying temperature is 37°C, the drying time is 5s, the hot pressing temperature is 40°C, the hot pressing time is 5s, and the hot pressing pressure is 5MPa.
[0282] Preparation of positive electrode
[0283] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed evenly in an appropriate amount of solvent N-methylpyrrolidone (NMP) in a mass ratio of 96.2:2.7:1.1 to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing, slitting, cutting and other processes.
[0284] Preparation of negative electrode sheet
[0285] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) are mixed evenly in an appropriate amount of solvent deionized water according to a mass ratio of 96.4:0.7:1.8:1.1 to obtain a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through the processes of drying, cold pressing, slitting and cutting.
[0286] Preparation of electrolyte
[0287] Ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:30:40 to obtain an organic solvent, and fully dried LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0288] Preparation of secondary batteries
[0289] The positive electrode sheet, the separator prepared above, and the negative electrode sheet are stacked and wound in sequence to obtain an electrode assembly, wherein the first base film in the separator faces the negative electrode; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, formation, shaping and other processes, a secondary battery is obtained.
[0290] The secondary batteries of Examples 2-18 and Comparative Example 1 are similar to Example 1, except that different base films are used or the parameters of the intermediate layer are adjusted. See Table 1 for details.
[0291] In the above embodiments and comparative examples, the melting points of the first base film and the second base film can be determined according to the following method: take 4 mg-6 mg of the sample to be tested, place it in the sample chamber of the differential scanning calorimeter, raise the temperature from 25°C to 400°C, and the heating rate is 10°C / min to obtain the melting endothermic curve of the sample. The temperature corresponding to the peak of the curve is the melting point of the sample.
[0292] In the above embodiments and comparative examples, the average pore diameters of the first base film and the second base film can be measured using a mercury porosimeter with reference to GB / T 21650-2008.
[0293] The volume distribution particle size Dv50 of the filler particles can be measured with reference to GB / T 19077-2016 particle size distribution laser diffraction method using a laser particle size analyzer (Mastersizer 2000E, Malvern, UK).
[0294] Test section
[0295] The following tests were performed on the separators and secondary batteries of Examples 1-18 and Comparative Example 1. The test results are shown in Table 2.
[0296] (1) Thermal shrinkage test of isolation film
[0297] Sample preparation: The isolation film prepared above was punched out into samples with a width of 50 mm and a length of 100 mm using a punching machine. Five parallel samples were placed on a glass plate and fixed.
[0298] Sample test: The temperature of the forced air oven is set to 250°C. After the temperature reaches the set temperature and stabilizes for 30 minutes, the glass plate is placed in the forced air oven and the time is set for 1 hour. After the time is up, the length of the isolation film is measured. The length value is marked as a in mm.
[0299] Calculation of heat shrinkage: heat shrinkage in the longitudinal direction (MD) = [(100-a) / 100] × 100%, and the average value of 5 parallel samples is taken as the test result.
[0300] (2) Puncture strength test of isolation film
[0301] The test was conducted with reference to GB / T 10004-2008. Specifically, the separator was cut into strips to obtain a 100mm wide test piece. The test piece was mounted on a sample clamp ring. A steel needle with a diameter of 1.0mm and a tip radius of 0.5mm was then used to puncture the test piece at a rate of (50±5)mm / min. The maximum load required for the needle to penetrate the test piece was measured. Five parallel groups of samples were collected, with three random points tested in each group. The arithmetic mean of the puncture strengths of all parallel samples was taken as the puncture strength of the separator.
[0302] (3) Air permeability test of isolation membrane
[0303] Refer to GB / T 36363-2018 to test the air permeability of the isolation membrane.
[0304] (4) Room temperature cycle performance test of secondary batteries
[0305] The secondary batteries prepared in the Examples and Comparative Examples were charged and discharged for the first time at 25°C. The process was as follows: After standing at 25°C for 30 minutes, the secondary batteries were charged at a constant current of 1C to 4.35V. Constant voltage charging continued until the current was ≤0.05C. The batteries were then discharged at a constant current of 1C to 2.8V. This constituted one charge-discharge cycle, and the discharge capacity at this point was recorded as the discharge capacity of the first cycle. This charge and discharge cycle was repeated, and the number of cycles until the capacity dropped to 80% was recorded.
[0306] (5) Energy density test of secondary batteries
[0307] At room temperature, the secondary battery is charged for the first time at a current of 1C, the charging is constant current and constant voltage charging, the termination voltage is 4.2V, and the cut-off current is 0.05C; the discharge is carried out at a current of 1C, the discharge termination voltage is 2.8V, and the discharge capacity C of the secondary battery at the first cycle is recorded. b And the discharge platform voltage U.
[0308] Use an electronic balance to weigh the mass m of the battery, and the energy density of the secondary battery is calculated using the following formula:
[0309] Energy density = C b *U / m.
[0310] Table 1
[0311] Table 2
[0312] It can be seen from the test results in Table 2 that when the isolation membrane includes a first base membrane with a high melting point, a second base membrane, and an intermediate layer located between the first base membrane and the second base membrane, and the average pore size of the first base membrane is within the range of the embodiments of the present application, the energy density and cycle performance of the battery can be significantly improved.
[0313] From the test results of Examples 1-6, it can be seen that when other conditions remain unchanged, as the average pore size of the first base membrane increases, the heat resistance and air permeability of the isolation membrane gradually improve. In addition, as the average pore size of the first base membrane increases, the energy density of the secondary battery also gradually increases. This may be because when the average pore size of the first base membrane is larger, it is conducive to increasing the embedding depth of the filler particles and the number of filler particles embedded in the first base membrane, thereby providing support capacity through the composite structure of the first base membrane and the filler particles, and reducing the overall thickness of the isolation membrane, thereby improving the cycle performance and energy density of the secondary battery. From the test results of Examples 3, 7-10, it can be seen that when other conditions remain unchanged, as the average pore size of the second base membrane increases, the heat resistance and strength of the isolation membrane decrease, but the air permeability of the isolation membrane and the energy density of the secondary battery improve. Therefore, the average pore size of the second base membrane can be adjusted according to actual needs so that the secondary battery has both good cycle performance and high energy density. Based on the test results of Examples 3, 15-18, it can be seen that, with other conditions remaining unchanged, increasing the porosity of the first base film improves the heat resistance, puncture strength, and air permeability of the separator, thereby simultaneously enhancing the cycling performance and extending the cycle life of the secondary battery. Furthermore, increasing the porosity of the first base film increases the number of filler particles embedded in the first base film, which helps reduce the overall thickness of the separator and further improves the energy density of the secondary battery.
[0314] In contrast, the average pore size of the first base film in the separator of Comparative Example 1 is smaller than that of the examples of the present application, making it difficult for filler particles to embed into the first base film. Consequently, not only is it difficult to form a composite structure with high mechanical strength, but it is also difficult to reduce the overall thickness of the separator. Consequently, the heat resistance and puncture strength of the separator of Comparative Example 1 are far inferior to those of Examples 1-18, and the energy density and cycling performance of the secondary battery of Comparative Example 1 are also unsatisfactory.
[0315] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and within the scope of the technical solution of the present application, embodiments having substantially the same structure as the technical idea and exerting the same effects are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be conceived by those skilled in the art to the embodiments, and other methods constructed by combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A separation film, comprising: A first base film, wherein the melting point of the first base film is above 175° C., and the average pore size of the first base film is ≥ 0.22 μm; Second basement membrane; as well as An intermediate layer is located between the first base film and the second base film, and the intermediate layer includes filler particles, at least part of which are embedded in the first base film.
2. The isolation film according to claim 1, wherein: The average pore size of the first base film is 0.22 μm-4.0 μm, and can be optionally 1.0 μm-2.7 μm.
3. The isolation film according to claim 1 or 2, wherein: The average pore size of the second base film is smaller than the average pore size of the first base film; Optionally, the average pore size of the second base film is 0.01 μm-0.5 μm, and more optionally 0.02 μm-0.1 μm.
4. The isolation film according to any one of claims 1 to 3, wherein: The embedding depth of the filler particles in the first base film is greater than or equal to 0.2 μm, and can be optionally 0.5 μm-1.0 μm.
5. The isolation film according to any one of claims 1 to 4, wherein: The embedding depth of the filler particles in the second base film is greater than or equal to 0.1 μm, and can be optionally 0.1 μm-0.5 μm.
6. The isolation film according to any one of claims 1 to 5, wherein: An embedding depth of the filler particles in the first base film is greater than an embedding depth of the filler particles in the second base film.
7. The isolation film according to any one of claims 1 to 6, wherein: The melting point of the first base film is greater than or equal to the melting point of the second base film; Optionally, the melting point of the first base film is 175°C-350°C, more preferably 220°C-350°C; Optionally, the melting point of the second base film is 130°C-200°C, more optionally 135°C-180°C.
8. The isolation film according to any one of claims 1 to 7, wherein: The longitudinal elongation at break of the first base film is 20%-105%, and can be 40%-90%; and / or, The transverse elongation at break of the first base film is 20%-105%, and can be optionally 40%-90%.
9. The isolation film according to any one of claims 1 to 8, wherein: The longitudinal elongation at break of the second base film is less than the transverse elongation at break of the second base film; The longitudinal elongation at break of the second base film is ≥40%, and can be 60%-150%; and / or, The transverse elongation at break of the second base film is ≥60%, and can be optionally 80%-160%.
10. The isolation film according to any one of claims 1 to 9, wherein: The porosity of the first base film is greater than the porosity of the second base film; Optionally, the porosity of the first base film is 50%-98%; Optionally, the porosity of the second base film is 20%-60%.
11. The isolation film according to any one of claims 1 to 10, wherein: The relative molecular mass of the first base film is greater than the relative molecular mass of the second base film; Optionally, the relative molecular mass of the first base film is 300,000-6,000,000, and more preferably 1,000,000-3,000,000; Optionally, the relative molecular mass of the second base film is 100,000-3,000,000, and more preferably 400,000-1,500,000.
12. The isolation film according to any one of claims 1 to 11, wherein: The ratio of the thickness of the first base film to the thickness of the second base film is 0.15-2.0, and can be 0.3-0.6; Optionally, the thickness of the first base film is 1 μm-10 μm, more preferably 1 μm-3 μm; Optionally, the second base film has a thickness of 2 μm-10 μm, more preferably 3 μm-6 μm.
13. The isolation film according to any one of claims 1 to 12, wherein: The air permeability of the first base film is lower than the air permeability of the second base film; Optionally, the ratio of the air permeability of the first base film to the air permeability of the second base film is 0.1-0.5, and more preferably 0.2-0.4; Optionally, the air permeability of the first base film is 20sec / 100cc-100sec / 100cc, and more preferably 30sec / 100cc-40sec / 100cc; Optionally, the air permeability of the second base film is 100sec / 100cc-300sec / 100cc, and more optionally 100sec / 100cc-150sec / 100cc.
14. The isolation film according to any one of claims 1 to 13, wherein: The puncture strength of the first basement membrane is less than the puncture strength of the second basement membrane; Optionally, the puncture strength of the first basement membrane is 20gf-150gf, and more preferably 20gf-80gf; Optionally, the puncture strength of the second base film is 60gf-400gf, and more optionally 80gf-270gf.
15. The isolation film according to any one of claims 1 to 14, wherein: The material of the first base film includes at least one of polytetrafluoroethylene and its derivatives, polyethylene terephthalate and its derivatives, polyimide and its derivatives, polyetheretherketone and its derivatives, polyphenylene sulfide and its derivatives, polybenzimidazole and its derivatives, polysulfone and its derivatives, and polylactic acid and its derivatives.
16. The isolation film according to any one of claims 1 to 15, wherein: The material of the second base film includes at least one of polyolefins, halogenated polyolefins, polyethers, polyesters, polyvinyl alcohol, polytetrafluoroethylene and its derivatives, polyethylene terephthalate and its derivatives, polyimides and their derivatives, polyetheretherketone and its derivatives, polyphenylene sulfide and its derivatives, polybenzimidazole and its derivatives, and polysulfone and its derivatives.
17. The isolation film according to any one of claims 1 to 16, wherein: The volume distribution particle size Dv50 of the filler particles is 0.01 μm-0.8 μm, and can be 0.2 μm-0.8 μm; and / or, The content of the filler particles is less than or equal to 90%, and can be 20%-80%, based on the total mass of the intermediate layer; and / or, The specific surface area of the filler particles is 2 g / m 2 -20g / m 2 , optional 6g / m 2 -9g / m 2 .
18. The isolation film according to any one of claims 1 to 17, wherein: The filler particles include at least one of inorganic particles, organic particles, and organic-metal framework materials; Optionally, the inorganic particles include one or more of inorganic particles having a dielectric constant of 5 or more, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions; Optionally, the organic particles include one or more of polycarbonate, polythiophene, polypyridine, polystyrene, polyacrylic wax, polyethylene, polypropylene, cellulose, cellulose modifier, melamine resin, phenolic resin, polyester, silicone resin, polyimide, polyamideimide, polyaramid, polyphenylene sulfide, polysulfone, polyethersulfone, polyetheretherketone, polyaryletherketone, and copolymer of butyl acrylate and ethyl methacrylate; Optionally, the organic-metal framework material includes one or more of a nitrogen-containing heterocyclic ligand building structure, an organic carboxylic acid ligand building structure, and a nitrogen-oxygen mixed ligand building structure.
19. The isolation film according to any one of claims 1 to 18, wherein: The intermediate layer further comprises a binder, and the binder comprises one or more of polyacrylate, polyacrylic acid, polyimide, polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-trichloroethylene copolymer, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, carboxymethyl cellulose, hydroxypropyl cellulose, regenerated cellulose, cellulose acetate, cellulose acetate propionate, cellulose acetate butyrate, polyacrylonitrile, polyvinyl alcohol, polyethylene, polypropylene, starch, cyanoethyl pullulan, thermoplastic polyurethane, maleic anhydride, and ethylene-acrylic acid copolymer; Optionally, the content of the binder is less than or equal to 35%, more preferably 10%-30%, based on the total mass of the intermediate layer.
20. The isolation film according to any one of claims 1 to 19, wherein: The isolation film satisfies at least one of the following (1)-(6): (1) The thickness of the isolation film is less than or equal to 7 μm, and can be 3 μm-6 μm; (2) The air permeability of the isolation film is 100sec / 100cc-300sec / 100cc, and can be optionally 120sec / 100cc-200sec / 100cc; (3) The transverse heat shrinkage rate of the isolation film at 250° C. for 1 hour is ≤1.0%, and can be optionally ≤0.4%; (4) The longitudinal heat shrinkage rate of the isolation film at 250° C. for 1 hour is ≤1.0%, and can be optionally ≤0.3%; (5) The transverse tensile strength of the isolation film is ≥0.5N, and can be 1.2N-3.5N; (6) The longitudinal tensile strength of the isolation film is ≥0.5N, and can be optionally 1.2N-3.5N.
21. A method for preparing the isolation film according to any one of claims 1 to 20, comprising the following steps: Providing a first base film, a second base film and an intermediate layer slurry including filler particles, wherein the melting point of the first base film is above 175° C., and the average pore size of the first base film is ≥0.22 μm; The intermediate layer slurry is coated on one of the first base film and the second base film and dried, and then laminated and hot-pressed with the other of the first base film and the second base film, so that at least part of the filler particles are embedded in the first base film, thereby obtaining a separator; Optionally, the slurry further comprises a binder.
22. The method according to claim 21, wherein: The method satisfies at least one of the following (1)-(5): (1) The drying temperature is 35°C-80°C, and can be 40°C-60°C; (2) The drying time is 5s-60s, and can be optionally 5s-15s; (3) The hot pressing temperature is 40°C-100°C, and can be optionally 40°C-70°C; (4) The hot pressing time is 5s-60s, and can be optionally 5s-10s; (5) The hot pressing pressure is 1MPa-10MPa, and can be optionally 3MPa-7MPa.
23. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator according to any one of claims 1 to 20, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet; Optionally, the first base film of the isolation film faces the negative electrode plate.
24. An electric device comprising the secondary battery according to claim 23.